Comitês de bioética e banco de amostras biológicas: uma reflexão jusfilosófica acerca do direito à liberdade de pesquisa científica - Patricia Gazire De Marco (2014)
The techno-scientific advances and the use of biological samples in research are growing increasingly and their main achievements started with the Human Genome Project. Therefore, it is important to create collections of biological samples, called biorrepositories or biobanks, to store these samples and also have a better control of them. The development of science led to unrestricted access to genetic information and it is necessary to protect the subject of the research. The aim of this work is to demonstrate the coexistence of the subjects and researchers freedom, considered fundamental rights. In addition, the bureaucratic procedures for creating bank of biological samples is inconsistent with the rationale of safeguards of those involved, since it does not necessarily protect the information or the person itself.